2012
DOI: 10.4014/jmb.1111.11010
|View full text |Cite
|
Sign up to set email alerts
|

Transfection Property of a New Cholesterol-Based Cationic Lipid Containing Tri-2-Hydroxyethylamine as Gene Delivery Vehicle

Abstract: A novel cholesterol-based cationic lipid containing a tri-2hydroxyethylamine head group and ether linker (Chol-THEA) was synthesized and examined as a potent gene delivery vehicle. In the preparation of cationic liposome, the addition of DOPE as helper lipid significantly increased the transfection efficiency. To find the optimum transfection efficiency, we screened various weight ratios of DOPE and liposome/DNA (N/P). The best transfection efficiency was found at the Chol-THEA:DOPE weight ratio of 1:1 and N/P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Cationic lipids, in general, are not part of the natural lipid pool. They have been synthesized for the special application of transfection [ 1 , 25 , 26 , 27 ]. Some of them are listed in Table 1 .…”
Section: Discussionmentioning
confidence: 99%
“…Cationic lipids, in general, are not part of the natural lipid pool. They have been synthesized for the special application of transfection [ 1 , 25 , 26 , 27 ]. Some of them are listed in Table 1 .…”
Section: Discussionmentioning
confidence: 99%
“…It can stabilize the surface membrane of LNPs, preventing premature release of nucleic acids by maintaining the integrity of the membrane, and promoting its circulation in the blood to extend the half-life of LNPs [90,97]. A study by Kim et al showed cholesterol enhanced gene transfection and biodistribution of mRNA-LNPs [98]. Furthermore, cholesterol concentration affects various LNP properties, including particle size, polydispersity, internalization, and overall structure.…”
Section: The Effect Of Structure Composition and Surface Modification...mentioning
confidence: 99%
“…In addition, the presence of polar groups in a quaternary ammonium head group region (such as guanidinium groups, [ 75 ] or hydroxy or amine groups in tocopherol, benzothiazole cationic lipid hybrids [ 76,77 ] ) generally increased the measured transfection efficiency, potentially due to increased hydrogen bonding between the cationic lipid and the nucleic acid molecule which can enhance uptake, as well as enhanced interactions between the cationic lipids and the typically anionic cell membrane resulting in increased cellular uptake. The conjugation of a naturally occurring molecule, such as a carotenoid molecule, [ 78 ] cholesterol (Figure 3B(i)), [ 79 ] lactic acid (Figure 3B(ii)), [ 80 ] or uracil (Figure 3B(iii)) [ 81 ] was also shown to improve the biocompatibility and increase transfection efficiency.…”
Section: Advances In Cationic Lipid Design: General Overviewmentioning
confidence: 99%
“…Similarly, the conjugation of cholesterol to a tri‐2‐hydroxyethylamine (THEA) head group via an ether linker resulted in the reasonably biocompatible cationic lipid Chol‐THEA (Figure 3B(i)). [ 79 ] Chol‐THEA:DOPE liposomes exhibited transfection efficiencies better than the commercially available lipids DOTAP, Lipofectamine, and DMRIE‐C in Huh‐7 cells, and similar or higher levels of transfection to these commercially available lipids in MCF‐7 cells. In another study, the naturally occurring molecule lactic acid (1‐hydroxy propyl group) was grafted to a quaternary ammonium bearing twin saturated, straight hydrocarbon chains of varying lengths (C8–C18) [ 80 ] to obtain biocompatible lipids.…”
Section: Advances In Cationic Lipid Design: a Detailed Overviewmentioning
confidence: 99%